(untitled) (Research, Society and Development, 2021)
Garlic (Allium sativum) is popularly used to flavor olive oil, it has high levels of allicin and selenium with antioxidant capacity and also phenolic compounds such as p-coumaric and caffeic acids. The present work evaluated the quality of extra virgin olive oil flavored individually with dryed and in natura garlic, both in the proportion of 10 % (w/w) during permanent infusion for 50 days at 60 ± 2⁰C. Analyzes were performed to determine the antioxidant activity, the total phenolic compounds content, the thermal stability and the main quality parameters by determining the acidity index, peroxide index, specific extinction coefficient by UV absorption, water activity (Aw), chlorophylls and carotenoids content. The results showed that the permanent infusion of dehydrated garlic (AOEVD) and fresh garlic (AOEVIN) in olive oil increased the antioxidant activity of the evaluated samples, preserved the content of total phenolic compounds during storage and delayed the degradation process of chlorophylls in relation to the control sample (AOEVP). The AOEVIN sample had the highest acidity index; the AOEVD showed the lowest Aw; the AOEVD and the AOEVIN reduced the peroxide index in relation to AOEVP. The addition of 10 % (w/w) dehydrated or in natura garlic permanently can increase the antioxidant capacity, the phenolic content and delay the degradation of chlorophylls in the olive oil.